A study of the early changes in hearts from diet-induced obese rats that may lead to cardiac dysfunction - Bezuidenhout, Nicole Joy (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.